2013
DOI: 10.1213/ane.0b013e318279b399
|View full text |Cite
|
Sign up to set email alerts
|

The TaperGuard™ Endotracheal Tube Intracuff Pressure Increase Is Less Than That of the Hi-Lo™ Tube During Nitrous Oxide Exposure

Abstract: During general anesthesia with N(2)O, the intracuff pressure of tapered endotracheal tube cuffs did not increase as rapidly as it did in conventional high-volume, low-pressure cuffs. The pressure in both types of cuffs increased rapidly when exposed to 66% N(2)O, and hence continuous or frequent monitoring is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
3
21
1
Order By: Relevance
“…The intracuff pressure in this study seems to be lower than that of a previously published simulation study [13]. The human trachea may not be as rigid as the model trachea; thus, we predict that the human tracheal wall relieves some of the increase in the intracuff pressure.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The intracuff pressure in this study seems to be lower than that of a previously published simulation study [13]. The human trachea may not be as rigid as the model trachea; thus, we predict that the human tracheal wall relieves some of the increase in the intracuff pressure.…”
Section: Discussioncontrasting
confidence: 63%
“…According to the manufacturer, the cylindrical cuff (Mallinckrodt TM Hi-Lo tracheal tube, Covidien, Ireland) and tapered cuff (Mallinckrodt TM TaperGuard tracheal tube, Covidien) are made of the same material, and have the same thickness. However, the intracuff pressure of the tapered cuff increased less than that of the cylindrical cuff during N2O exposure in simulation conditions [13]. tapered cuff increased less than that of the cylindrical cuff during N2O exposure, the cuff shape would be a cause of the difference in intracuff pressure, and an ETT with a tapered cuff would be a good choice for tracheal intubation during general anesthesia using N2O.…”
Section: Introductionmentioning
confidence: 84%
“…2,5,6 The intracuff pressure can be affected by various factors, including environmental factors (e.g., intraoperative use of high airway pressure and nitrous oxide), patient factors (e.g., differences in the size of the trachea and the position of the intratracheal cuff), and cuffrelated factors (e.g., differences in cuff compliance and diameter). [7][8][9][10] Positional change and neck movement after intubation can displace an ETT in a patient's trachea. [11][12][13][14][15][16][17][18] Intratracheal migration of the ETT due to a change in patient positioning can result in a change in the ETT cuff pressure because the trachea is not cylindrical.…”
Section: Résumémentioning
confidence: 99%
“…18 In the present study, the smaller increase in cuff pressure together with a greater increase in cuff volume in the tapered cuff compared with the cylindrical cuff might be explained by the relatively large compliance and the uneven distribution of volume in the cylindrical cuff. 17,18 The findings of the present study suggest that the tapered cuff has the advantage of increased preservation of tracheal mucosal perfusion, associated with a smaller increase in cuff pressure, compared with the cylindrical cuff during surgery. Yildirim et al 7 reported that pneumoperitoneum and the reverse-Trendelenburg position increased TT cuff pressure during anaesthetic maintenance with 1-2% sevoflurane and 66% air in oxygen.…”
Section: Discussionmentioning
confidence: 44%
“…However, in the present study the maximum cuff pressure recorded was $30 cm H 2 O; this may have been the result of differences between the lung model and the human trachea, including the warm body temperature, gas diffusion through mucosal membranes and the lower compliance of the human trachea. 18,20 Pneumoperitoneum with position change during laparoscopic surgery has been reported to induce an increase in peak inspiratory pressure and a decrease in the distance between the TT and the carina. [21][22][23] In the present study, cephalic displacement of the TT tip was observed without endobronchial intubation.…”
Section: Discussionmentioning
confidence: 99%